The reduced SCFA-producing gut microbes are involved in the inflammatory activation in Kawasaki disease - Wang, Fangyan; Qian, Fanyu; Zhang, Qihao; Zhao, Jian; Cen, Jianke; Zhang, Jiamin; Zhou, Jinhui; Luo, Ming; Jia, Chang; Rong, Xing; Chu, Maoping (Frontiers in Immunology, 2023)
Kawasaki disease (KD), an acute febrile systemic vasculitis in children, has become the leading cause of acquired heart disease in developed countries. Recently, the altered gut microbiota was found in KD patients during the acute phase. However, little is known about its characteristics and role in the pathogenesis of KD. In our study, an altered gut microbiota composition featured by the reduction in SCFAs-producing bacteria was demonstrated in the KD mouse model. Next, probiotic Clostridium butyricum (C. butyricum) and antibiotic cocktails were respectively employed to modulate gut microbiota. The use of C. butyricum significantly increased the abundance of SCFAs-producing bacteria and attenuated the coronary lesions with reduced inflammatory markers IL-1β and IL-6, but antibiotics depleting gut bacteria oppositely deteriorated the inflammation response. The gut leakage induced by dysbiosis to deteriorate the host’s inflammation was confirmed by the decreased intestinal barrier proteins Claudin-1, Jam-1, Occludin, and ZO-1, and increased plasma D-lactate level in KD mice. Mechanistically, SCFAs, the major beneficial metabolites of gut microbes to maintain the intestinal barrier integrity and inhibit inflammation, was also found decreased, especially butyrate, acetate and propionate, in KD mice by gas chromatography-mass spectrometry (GC-MS). Moreover, the reduced expression of SCFAs transporters, monocarboxylate transporter 1 (MCT-1) and sodium-dependent monocarboxylate transporter 1 (SMCT-1), was also shown in KD mice by western blot and RT-qPCR analyses. As expected, the decrease of fecal SCFAs production and barrier dysfunction were improved by oral C. butyricum treatment but was deteriorated by antibiotics. In vitro, butyrate, not acetate or propionate, increased the expression of phosphatase MKP-1 to dephosphorylate activated JNK, ERK1/2 and p38 MAPK against excessive inflammation in RAW264.7 macrophages. It suggests a new insight into probiotics and their metabolites supplements to treat KD.